"I was able to take it back": Seeking VBAC after experiencing dehumanizing maternity care in a primary cesarean - Bridget Basile Ibrahim; Melissa Cheyney; Saraswathi Vedam; Holly Powell Kennedy (Elsevier, 2023)
In this article, we present findings from a qualitative narrative analysis that examined the pregnancy, primary cesarean, and subsequent birth experiences of women in the United States. Using a maximal variation sampling strategy, we recruited participants via social media and networking to participate in semistructured interviews. Twenty-five women from diverse backgrounds and geographic locations across the U.S. participated, eight self-identified as racialized and seventeen as non-Hispanic, White. Data were analyzed iteratively using Clandinin and Connelly's approach to Narrative Inquiry. Across their narratives, participants described their experiences of maternity care that were either generally negative (dehumanizing care) or positive (humanized care). They further described how their experiences of dehumanizing or humanized care impacted their decision-making for subsequent births, mental health, relationships with the healthcare system, early parenting birth satisfaction, and family planning. Findings suggest that regardless of ultimate mode of birth, what was most important to women was how they are treated by their maternity care team. We suggest practice changes that may improve the experience of maternity care for primary cesarean and subsequent births, especially among those made marginal by systems of oppression.